Digital Information Media of the Salman ITB Halal Center in improving Marketing Performance of Halal Lecture Program - Raditya Pratama Putra; Indri Rachmawati; Yuristia Wira Cholifah (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2021)
The community can make wise use of the existing communication media as well as the growing communication media. The era of connectivity brought many changes to the communication media which is currently known as digital media. Digital media provides many opportunities and advantages for finding and sharing information. The purpose of this research is to look at the digital communication media used in the Halal Lecture program and to see the digital marketing communication process carried out by the Halal Salman ITB center regarding the Halal Lecture program. The research method used is qualitative with a case study approach. As for the results of this research, the digital information media Instagram is used by the Salman Halal Center ITB to inform and market the Halal Lecture program by paying attention to the elements of the message's purpose. Information and persuasion is conveyed through an e-flyer posted on the official Instagram @salmanitb. Not only that, the public also participates in digital marketing through Whatsapp broadcast messages, personal Instagram stories and Whatsapp stories. Ease of access and reach of digital media are benefits that can be obtained by users, therefore digital media can be applied in various fields of activity ranging from education, campaigns, entertainment, to marketing.